2018
DOI: 10.1002/mmce.21455
|View full text |Cite
|
Sign up to set email alerts
|

Charge density and bare surface barrier height in GaN/AlGaN/GaN heterostructures: A modeling and simulation study

Abstract: In this article, we present a physics‐based model to explain the effect of the GaN cap layers on the 2D electron gas density and the bare surface barrier height in AlGaN/GaN heterostructures. We consider that the 2DEG originates from the surface donor states present on the GaN cap top surface. The influence of a 2D hole gas, formed when the valence band crosses the Fermi energy level, has also been considered. This model agrees well with the published experimental results and TCAD simulations, and can easily b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…In fact, the existence of such a high-density 2DHG in a GaN/AlGaN/GaN heterostructure is experimentally shown [32]. Modeling the effect of the 2DHG in a GaN/AlGaN/GaN is reported [33,34]. Again, Chen et al [26] have experimentally demonstrated a hole accumulation at the heterointerface due to a strong piezoelectric polarization effect in the InGaN/GaN heterostructure.…”
Section: Ingan Sp Sp Pementioning
confidence: 98%
“…In fact, the existence of such a high-density 2DHG in a GaN/AlGaN/GaN heterostructure is experimentally shown [32]. Modeling the effect of the 2DHG in a GaN/AlGaN/GaN is reported [33,34]. Again, Chen et al [26] have experimentally demonstrated a hole accumulation at the heterointerface due to a strong piezoelectric polarization effect in the InGaN/GaN heterostructure.…”
Section: Ingan Sp Sp Pementioning
confidence: 98%
“…In addition, diodes made of silicon as a representative generation of semiconductor materials are more serious in high temperature environments, thus limiting their application range [126,127]. As a third-generation semiconductor material, gallium nitride has the advantages of high electron mobility, high working bandwidth, short response time and high temperature resistance, which has great development potential [128,129]. Diodes or gallium nitride high electron mobility transistors (GaN HEMTs) made from gallium nitride materials have high application value in metamaterials.…”
Section: Efficient Control Of Terahertz Metamaterialsmentioning
confidence: 99%
“…An extensive mathematical analysis of extrinsic capacitance influence on GaN HEMT investigated by Crupi G et al 7 A new small signal model based on Bayesian inference theory developed for GaN-HEMT 8 and a physics-based model developed by J.Ghosh et al for charge density and surface barrier height for GaN-HEMTs. 9 Empowered GaN HEMT models are developed by G. Crupi et al for power amplifier design. 10 Pulsed I-V and S-parameter measurement systems developed for isodynamic characterization for GaN HEMTs.…”
Section: Introductionmentioning
confidence: 99%
“…Further improving the device performance of III‐nitride HEMTs, optimization of the device structure is needed. An extensive mathematical analysis of extrinsic capacitance influence on GaN HEMT investigated by Crupi G et al 7 A new small signal model based on Bayesian inference theory developed for GaN‐HEMT 8 and a physics‐based model developed by J.Ghosh et al for charge density and surface barrier height for GaN‐HEMTs 9 . Empowered GaN HEMT models are developed by G. Crupi et al for power amplifier design 10 .…”
Section: Introductionmentioning
confidence: 99%